EL DESARROLLO SUSTENTABLE Y LA INSTRUMENTACIÓN DEL PARADIGMA EN MÉXICO - Luis C. Santander-Botello; Luis M. Mejía-Ortíz; Marilú López-Mejía (European Scientific Journal, ESJ, 2015)
Since the late 1960s the discussion about the limits of growth fueled the development of sustainable development as a paradigm that has dominated strategies and policies, including the proposal in 2012 of Green Economies. Nonetheless, progress has not been achieved, among other reasons for the absence of integrated public policies. With a general perspective, the experience of Mexico’s federal public administration and recent planning instruments is revisited, including the creation of green jobs. With such analysis the conclusion about the importance of integrated public policies is duplicated.